Motives and Satisfaction of Radio Listeners in The New Media Era (Cases Study on Dhara FM Radio Listenes in Pariaman) - Fitriani Ayu Lestari; Sarwan Sarwan; Mulyanti Syas; Prima Kurinati Hamzah (Universitas Islam Negeri Imam Bonjol Padang, 2019)
Radio is the oldest and most flexible electronic mass media. The new media as mentioned has resulted in the radio being abandoned by the audience and turning to choosing new media as information and entertainment. Survey conducted by a Nielsen survey institute in 2014, stated that every year radio listeners decreased by 3%. The purpose of this study is to find out and explain the motives and satisfaction of the Dhara FM radio listeners in the city of Pariaman in listening to radio in the new media era. This study uses descriptive quantitative research methods. Describe systematically, factually, and accurately about the facts and nature of the population and try to describe phenomena in detail. The data source is a questionnaire. The analysis used is descriptive analysis. Results that can be taken from this study are entertainment motives and the motives of interaction and social integration have a significant influence in influencing the satisfaction of the Dhara FM radio listeners Pariaman. Satisfaction obtained by listeners can be seen from the persistence of radio listeners in listening to the radio. Motives have a strong enough influence to achieve listener satisfaction.